Usability Analysis of a Medication Visualization Tool for Decision Support - Schmidtchen, Leon; Villis, Marten; Christoph, Jan; Rödle, Wolfgang (German Medical Data Sciences 2023 – Science. Close to People., 2023)
BACKGROUND: In Germany, patients are entitled to a medication plan. While the overview is useful, it does not contain explicit information on various potential adverse drug events (ADEs). Therefore, physicians must continue to seek information from various sources to ensure medication safety. OBJECTIVE: In this project a first functional prototype of a medication therapy tool was developed that focuses on visualizing and highlighting potential ADEs. A usability analysis about the tool's functionality, design and usability was conducted. METHODS: A web application tool was developed using the MMI Pharmindex as database. ADEs are color coded and can be displayed in three different ways - as a list, a table, or a graph. To test the tool, an online survey was conducted amongst healthcare professionals (n = 9). The test included two real medication plans to check ADEs through the tool. RESULTS: The survey results indicated that the web tool was clear and self-explanatory. It scored overall "good" (score: 76.5) on the System Usability Scale questionnaire. Due to the free-text information of the database used, there were some inconsistencies in the visualized ADEs. CONCLUSION: There is a demand for a visualization tool for medications. The high quality of the database is crucial in order to correctly visualize all necessary information, such as drug-drug interactions and inclusion of patient data. This is essential to provide a trustworthy tool for medical professionals.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Adverse Drug Event; Data Visualization; Drug-drug Interaction; Medication Information; Usability Analysis